2014
DOI: 10.1016/j.nimb.2013.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Application of X-ray microtomography to study the influence of the casting microstructure upon the tensile behaviour of an Al–Si alloy

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 14 publications
0
36
0
1
Order By: Relevance
“…Such unmelted zones are observed in the bulk or in sub-surface areas. As the position of the defects respectively to the surface is an influencing parameter on the crack initiation time, as shown in the case of shrinkage in casting alloys [4,5], this has an impact on the criticality and the lifetimes. In the case of unmelted zones, one can observe in Figure 3 that the fatigue properties are qualitatively slightly better for the specimens built in the XY direction.…”
Section: Discussion and Comparison With Casting Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…Such unmelted zones are observed in the bulk or in sub-surface areas. As the position of the defects respectively to the surface is an influencing parameter on the crack initiation time, as shown in the case of shrinkage in casting alloys [4,5], this has an impact on the criticality and the lifetimes. In the case of unmelted zones, one can observe in Figure 3 that the fatigue properties are qualitatively slightly better for the specimens built in the XY direction.…”
Section: Discussion and Comparison With Casting Processesmentioning
confidence: 99%
“…In fact, in the case of casting alloys, it has been shown that a simple 2D analysis (size, morphology) from data extracted from surface images of such complex 3D defects is generally not sufficient to understand and quantify their impact on crack initiation mechanisms and on lifetime, even if some statistical corrections are possible [11]. Therefore, a systematic 3D quantitative analysis of the specimens microstructure by CT-tomography (as conducted in [6]) could be a direct perspective of this work, associated to in-situ fatigue tests as in [4,5].…”
Section: Discussion and Comparison With Casting Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly used methods to detect internal casting defects are X-rays, the tightness test, ultrasonic testing or the eddy current technique [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…• C for 200 h. A full 3D characterization of the microstructure through X-ray tomography [2] is performed in order to measure the size and shape distribution of pores in a Representative Elementary Volume while 2D analyses are also carried out on samples cut from the same cylinder a Corresponding author: fabien.szmytka@mpsa.com This is an Open Access article distributed under the terms of the Creative Commons Attribution License 4.0, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.…”
Section: Introductionmentioning
confidence: 99%